Socio-cultural perceptions toward blood donation practice among young blood donors - Sulaiman, Szariannie; Mustari, Sohela; Eid, Iyad M. Y. (Secholian Publication, 2023)
This is a qualitative study examining the socio-cultural perception toward blood donation practice among young blood donors. Understanding blood donation practice and its underlying socio-cultural perceptions among the younger population is crucial to the functioning of the health system. This is to ensure blood supply is adequate to address the health needs of the population. To address the issue, nine (9) young blood donor aged between 21 and 24 years old were approached during a blood donation drive held at the International Islamic University Malaysia. These young blood donors were selected through a convenient sampling technique. Guided by a semi-structured interview schedule, face-to-face interviews were conducted on campus to capture informants’ perceptions toward blood donation practice. Thematic analysis technique was used to analyse data obtained from the study. It was found that young blood donors in this study perceive blood donation practice as a good thing to do to help others. This includes perceiving blood donation practice as moral and social responsibilities.